(untitled) (Research, Society and Development, 2022)
The child with cancer in the terminal phase requires special attention not only because of the finitude of life, but particularly because of their understanding phase and the need for painful procedures. It aims to understand the nurse’s care for hospitalized children with oncological diseases beyond the possibility of cure. To carry out the present study, the bibliographic research method was used in the search for scientific articles, consulting the online databases BDENF, Lilacs and Google academic, covering the search between 2015 and 2020. The study showed two categories: perceptions and reactions emotional aspects of nursing professionals who assist children with cancer and safety management and nursing care in pediatric oncology. It is concluded that the nurse is a multifaceted professional with different skills and attributions, where childhood cancer causes a series of changes, including changes in functional, physical, mental and psychological capacity in the performance of this professional, always needing to implement self-care strategies through your assistance provided.